Integrating AI in Physical Education: An Analysis of Potential and Practice - Ira Arini; Dedi Aryadi; Ayi Rahmat; Lukmanul Hakim; Dodi Nurhidayat; Ahmad Firmansyah (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The purpose of study: The fusion of AI (Artificial Intelligence) technology with physical education is an emerging field that holds the promise of revolutionizing how PE (Physical Education) is taught and learned. This review examines the current landscape and future prospects of Artificial Intelligence applications within Physical Education settings. Materials and methods: Exploring various Artificial Intelligence in physical education, such as machine learning, data analytics, and intelligent systems that have the potential to personalize learning, improve athletic performance, and offer innovative teaching methodologies. By assessing recent studies and technological advancements, it can be known how Artificial Intelligence can provide real-time feedback and objective assessments of students' performances. Research method: This article uses Systematic Literature Review (LSR) method, namely reviewing several studies of the integrating AI in physsical education sourced from several research results that have been carried out using certain criteria such as search strategy, inclusion criteria, data extraction, and quality asesment. Results and conclusions: The comperhensive search began on April 19, 2024 and ended on May 30, 2024 and identified 200 articles, of which 11 were included in the systematic review whos the flow chart of screening according to PRISMA guidelines. The paper discusses the ethical considerations and necessary technical proficiencies required for Physical Education professionals to effectively incorporate Artificial Intelligence into their pedagogy. The article concludes by pinpointing future research directions to ensure the efficient and responsible adoption of Artificial Intelligence in the field of physical education. It can be concluded that in research using experimental methods, the used of Artificial Intelligence had a positive influence on the treatment group, including learning outcomes, teacher skills, motivation, motor skills and other subject skills.